Establishment of a prediction model for major adverse cardiovascular and cerebrovascular events in prehypertensive patients - HE Zhi,an，LAI Jiangqiong，ZHENG Tao (Zhongguo linchuang yanjiu)
Objective To explore the predictive efficacy of logistic regression model based on carotid artery elastic ultrasound parameters for the occurrence of major adverse cardiovascular and cerebrovascular events（MACCE ）in patients with prehypertension. Methods The clinical data of 100 prehypertensive patients treated at the 910th Hospital，Joint Logistic Support Force，Chinese People's Liberation Army from January 2019 to January 2023 were retrospectively analyzed. After 1-year follow-up，patients readmitted due to MACCE were assigned to the MACCE group，while others to the non-MACCE group. Multivariate logistic regression analyses was performed to identify risk factors. A logistic regression model was constructed ，and its predictive performance was evaluated using the area under the receiver operating characteristic（ROC）curve（AUC）.Results The incidence of MACCE was 23.00%（23/100）. Multivariate logistic analysis confirmed that smoking history，high-salt diet，diabetes，carotid intima-media thickness（IMT），maximum carotid artery diameter（Dmax），minimum carotid artery diameter（Dmin），stiffness index(β), vascular elastic dilation coefficient（FEK），arterial compliance（AC），and pulse wave velocity（PWV）were independent influcencing factors（P<0.05）.The logistic model was：Y=-5.283+1.715（IMT）+1.856（Dmax）+1.693（Dmin）+1.871(β)- 1.506（FEK）- 1.769（AC）+ 2.014（PWV）. The sensitivity，accuracy，positive predictive value and AUC of this model for predicting the occurrence of MACCE in prehypertension patients were 91.86%，90.74%，89. 15% and 0.924，respectively. Conclusion The logistic regression model incorporating Dmax，Dmin，β, FEK，and other risk factors demonstrates high sensitivity and accuracy in predicting MACCE among prehypertensive patients，with robust clinical applicability.